Die wysgerige agtergrond van die Hervormde teologiese opleiding aan die Universiteit van Pretoria - Dreyer, P. S. (Hervormde teologiese studies, 1989)
The philosophical background of the theological training of the Nederduitsch Hervormde Church of Afrika at the University of Pretoria Since the inception of the theological training of the Nederduitsch Hervormde Church of Africa at the University of Pretoria in 1917 philosophy has been a mandatory subject for all propaedeutic theological students. The history of the Department of Philosophy is traced to show the prevalent types of philosophy taught in the Department, because the philosophical training is considered important as preparation for theological training.